Beyond Conceptual Ambiguity: Exemplifying the "Resistance Pyramid" Through the Reflections of (Ex) Prisoners’ Agency - Munn, Melissa; Bruckert, Chris (Qualitative Sociology Review, 2010)
Contemporary resistance scholarship increasingly positions individuals as agents operating within power relations and as such, this stimulating and diverse body of work illuminates the complexity of powerresistance. The richness of this academic engagement notwithstanding, there continues to be a paucity of work which offers a framework for conducting an analysis of resistance. In this article, we propose a general framework through which power-resistance can be coded, analyzed and theorized. Using data from an ethnomethodological study of 20 former longterm male prisoners in Canada, we demonstrate the usefulness of our 'resistance pyramid' to render visible the objectives, purposes, strategies, tactics and skills which characterize the processes, and not just the practices, of resistance. We argue that it is exactly these, often obscured, processes that allow us to appreciate the density of resistance-power, the multiple ways it operates and the significance of individuals' social, personal or political capital.